Ultrasensitive and highly selective Co2+ detection based on the chiral optical activities of L-glutathione-modified gold nanoclusters - Ding, Qi; Wang, Fang; Yang, Weimin; Xing, Xinhe; Lin, Hengwei; Xu, Liguang; Li, Si (Frontiers in Chemistry, 2024)
Developing highly sensitive and selective detection methods is crucial for environmental and healthcare monitoring. In this study, the chiral and fluorescent signals of L-glutathione-modified gold nanoclusters (L-GSH-Au NCs) were discovered to be responsive to Co 2+ , which displayed linear correlations with the concentration changes of Co 2+ . Notably, the chiral signal was more sensitive than the FL signal, whose limit of detection (LOD) was calculated to be 0.37 μM and 3.93 times lower than the LOD obtained with fluorescent signals. Moreover, the chiral signals exhibited unexpectedly high selectivity towards Co 2+ , effectively avoiding interference from other metal ions and biomolecules. Furthermore, the concentrations of Co 2+ in various samples, such as Taihu water, tap water, bottled water, and animal serum, were accurately quantified using the chiral signals of L-GSH-Au NCs without complex pretreatment, with recoveries ranging between 95.64% and 103.22%. This study not only provides an innovative approach for Co 2+ detection but also highlights the detection capabilities of chiral signals in complex environments.